ANALISIS PERKEMBANGAN PEGADAIAN SYARIAH DI INDONESIA - Novita Dwi Safitri; Asiah Wati (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2023)
Abstract: Problems that often occur in society are economic problems. The community is in a condition where the community only has assets in the form of non-cash but at the same time the community needs funds in the form of cash. This is where the pawn shop comes into play. This article was written to obtain information regarding the development of sharia pawnshops until the emergence of digital sharia pawnshops in Indonesia by applying a qualitative descriptive method and reviewing several references and literature to obtain the required study data. The result of writing is that in Indonesia there are sharia pawnshop institutions that facilitate the community with sharia pawn services. Along with the times, sharia pawnshops continue to develop their business by releasing digital sharia pawnshops in the form of applications and websites. However, the application is not completely perfect. Even though it has several advantages, this service still has disadvantages as well. The advantages of digital sharia pawnshops include 1) making transactions easier for customers; 2) effective in terms of time and cost, 3) information can be known in real time, 4) transactions without having to queue, 5) the features offered are quite complete. However, the drawbacks of this application are 1) it requires a strong internet network so that transactions can run smoothly, 2) not all customers are in an environment with an adequate internet network, 3) not all customers are technologically literate, 4) it allows for cyber data or hacking, 5) rating on Google Play is still low at 2.8. It is hoped that these things can become constructive criticism and suggestions for various parties, especially for parties from sharia pawnshops so that they can provide more excellent and maximum service in the current era.   Abstrak: Permasalahan yang kerap terjadi dalam masyarakat adalah permasalahan ekonomi. Masyarakat berada pada kondisi dimana masyarakat hanya memiliki harta dalam bentuk tidak tunai tetapi saat bersamaan dengan itu masyarakat membutuhkan dana dalam bentuk uang tunai. Di sinilah pegadaian mengambil peran. Artikel ini ditulis untuk mendapatkan informasi mengenai perkembangan pegadaian syariah hingga munculnya pegadaian syariah digital di Indonesia dengan menerapkan metode deskriptif kualitatif dan mengkaji beberapa referensi serta literatur guna mendapatkan data kajian yang dibutuhkan. Hasil penulisan adalah di Indonesia terdapat lembaga pegadaian syariah yang memfasilitasi masyarakatnya dengan layanan gadai syariah. Seiring dengan perkembangan zaman, pegadaian syariah terus mengembangkan usahanya dengan merilis pegadaian syariah digital dalam bentuk aplikai dan website. Namun, dalam aplikasi tersebut belum sepenuhnya sempurna. Meskipun telah memiliki beberapa kelebihan, layanan ini masih memiliki kekurangan pula. Kelebihan dari pegadaian syariah digital antara lain 1) memudahkan nasabah dalam bertransaksi; 2) efektif dari segi waktu dan biaya, 3) informasi dapat diketahui secara realtime, 4) bertransaksi tanpa harus mengantre, 5) fitur yang ditawarkan cukup lengkap. Namun, kekurangan dari aplikasi ini adalah 1) memerlukan jaringan internet yang kuat agar transaksi dapat berjalan lancar, 2) tidak semua nasabah berada di lingkungan dengan jaringan internet yang memadai, 3) tidak semua nasabah telah melek teknologi, 4) memungkinkan adanya cyber data atau peretasan, 5) rating di Google Play masih rendah yaitu 2,8. Hal-hal tersebut diharapkan mampu menjadi kritik dan saran yang bersifat membangun bagi berbagai pihak terkhusus bagi pihak dari pegadaian syariah agar semakin memberikan pelayanan yang prima dan maksimal di era sekarang ini.